Similar Attitudes, Different Strategies: A Limited Survey of the Discourse Strategies to Oppose Genetically Modified Organisms Conspiracy Theories by Chinese Scientist Communicators and Citizen Communicators on Zhihu - Yang, Zheng (Frontiers in Psychology, 2022)
The development of the digital media environment has led to a diversification in the role of science communicators. Both scientists and non-scientist citizens can act as science communicators in relation to online discussion of genetically modified organisms (GMOs). Through a limited study, based on thematic and open coding of 60 answers provided by scientist science communicators and citizen science communicators on GMOs on Zhihu, the biggest Chinese knowledge sharing network, it has been found that “business conspiracy theories” about GMOs are the most mentioned and discussed theories, followed by the conspiracy theory of “GMOs as state control tool” on Zhihu. Both citizen science communicators and scientist science communicators are inclined to show oppositional attitudes to GMOs conspiracy theories on Zhihu, despite the differences in their scientific backgrounds; however, they use very different discourse strategies. Citizen science communicators tend to use “lay logic” with more rhetoric, while scientist science communicators tend to use direct scientific knowledge and logic with less rhetoric.